Impact of high density mapping using a grid shaped catheter with orthogonal signal analysis on ventricular tachycardia ablation strategy. (24th May 2021) - Roca, I; Lorgat, F; Haqqani, H; Lacotte, J; Roithinger, F; Fiedler, L; Miller, A; Steven, D
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: Ventricular tachycardia (VT) in patients with structural heart disease (SHD) is related to scar and slow conduction areas. Substrate-based ablation has become the gold standard treatment in patients with SHD-related refractory VT. A new high-density grid shaped catheter that allows simultaneous analysis of adjacent orthogonal bipolar signals can allow better understanding of these slow conduction areas with the potential to improve ablation results. Purpose: This was a prospective, multicenter observational study to characterize the utility of electroanatomical mapping with a high density grid-style mapping catheter (HD Grid) in subjects undergoing catheter ablation for ventricular tachycardia (VT) in real-world clinical settings. Methods: During the study period, patients who underwent VT ablation using the HD Grid catheter as the primary mapping catheter were included. Comparisons both during the procedure and retrospectively were performed between conventional electrode configuration maps and simultaneous orthogonal bipole electrode configuration maps. The influence of these different configurations on ablation strategy was analyzed. Results: During study period (January 2019 – April 2020) 57 maps were performed in 34 VT subjects (average age: 64.3yr, male: 85.3%, ischemic cardiomyopathy: 70.6%). The left ventricle was mapped in 94.1% of subjects, including left ventricular outflow tract and papillary muscles in 20.6% and 8.8% respectively, reporting minimal or no ectopic beats in 97.1% of the subjects. The total number of mapping points collected was 14172.0 ± 15174.8 in 24.3 ± 17.9 min per map. Simultaneous orthogonal bipole mapping identified differences in 67.6% of maps compared to linear along-the-spline electrode configurations. The differences consisted mainly in the surface area (92%) and location of low voltage (40%). When compared during the procedure, simultaneous orthogonal bipole mapping was used to identify ablation strategy in 100% of cases. When compared to a standard along-the-spline configuration retrospectively, the ablation strategy identified with simultaneous orthogonal bipoles was different in 30.1% of cases. The ablation strategy used in these subjects was mainly substrate ablation (late potentials and low voltage areas in scar regions) with an acute success rate of 97.1%. Conclusions: The use of the HD Grid catheter with the ability to analyze orthogonal signals is feasible and has the potential to change the ablation strategy in one third of VT patients with a high acute success rate.